Deficient arsenic methylation and global proteomic reprogramming in human keratinocytes during arsenic-induced skin carcinogenesis - Alexandra N. Nail; Mayukh Banerjee; Manting Xu; Caitlin H. Reynolds; Miroslav Stýblo; Peter H. Cable; Daniel W. Wilkey; Michael L. Merchant; Ana P. Ferragut Cardoso; Shelia D. Thomas; J. Christopher States (Archives of Toxicology, 2026)
Chronic inorganic arsenic (iAs) exposure affects > 220 million people worldwide and skin cancer is a hallmark of long-term iAs exposure. Limited information exists regarding arsenic methylation by human keratinocytes and how methylation influences skin carcinogenesis. Inorganic arsenite (iAs III ) and its methylated metabolites disrupt diverse zinc finger proteins, leading to differential toxicity patterns. We examined arsenic methylation capacity in non-malignant human keratinocytes and interrogated proteomic remodeling across three stages of iAs III induced malignant transformation using the well-established preclinical HaCaT model. Arsenic methylation was assessed by hydride generation cryotrapping inductively coupled-mass spectrometry and global proteomic changes were analyzed by tandem-mass tagging liquid chromatography-tandem mass spectrometry. Primary, hTERT-immortalized and HaCaT human keratinocytes exhibited negligible arsenic methylation, with iAs III comprising at least 98.5% of total intracellular arsenic, attributable to minimal expression of arsenite methyltransferase. Proteomic profiling identified over 275 differentially expressed proteins at each stage of transformation, including multiple zinc finger proteins implicated in cell cycle control, RNA metabolism, and genome stability. Ingenuity® Pathway Analysis revealed progressive, coordinated disruption of cancer-associated pathways and regulatory networks over the transformation timeline, including zinc-coordinating upstream regulators that may explain widespread pathway dysregulation. Collectively, our findings suggest that iAs III promotes skin carcinogenesis by disrupting C3H1- and C4-type zinc finger protein-centered regulatory networks that coordinate cancer-associated signaling and metabolic pathways in human keratinocytes, highlighting key candidates for future mechanistic studies.

Stability Specifications for Climate Data Records: Their Meaning and Application in Evaluating Geophysical Trend Uncertainty - Christopher J. Merchant; Emma R. Woolliams; Wouter Dorigo; Claire E. Bulgin; Kevin Gobron; Roland Hohensinn; Xavier Loizeau; Connor P. J. Tynan (Surveys in Geophysics, 2026)
When quantifying changes over time in the natural environment, the stability of the observations used should be considered. Stability conceptually refers to how accurately true geophysical changes and trends are reflected in observational data. We argue the need for a better approach to defining and quantifying stability consistently across climate data records. We propose that the appropriate stability metric is the stability uncertainty for specified spatial and temporal scales. We formally define stability uncertainty by analogy with metrological measurement uncertainty. Informally, stability uncertainty informs data analysts about the plausible magnitude of a non-geophysical contribution to trend values arising solely from the observing system. Neglecting the stability uncertainty leads to overconfident assessment of the significance of geophysical trends inferred from observations. We recommend that adopting this metric would greatly improve the clarity and practical impact of the Global Climate Observing System (GCOS) statements of requirement for stability of essential climate variable (ECV) products. Moreover, GCOS stability requirements would then become a useful resource for users of ECV products when evaluating and interpreting trends in observations, helping them avoid unjustified claims for the significance of computed trends; a synthetic illustration of such usage is provided.

A Unified Framework for Trend Uncertainty Assessment in Climate Data Records: Demonstration on Global Mean Sea Level - Kevin Gobron; Roland Hohensinn; Xavier Loizeau; Claire E. Bulgin; Christopher J. Merchant; Emma R. Woolliams; Maurice G. Cox; Wouter Dorigo; Thomas Howard; Mary Langsdale; Adam C. Povey; Michaël Ablain; et al. (Surveys in Geophysics, 2026)

Making Sense of Uncertainties: Ask the Right Question - Alexander Gruber; Claire E. Bulgin; Wouter Dorigo; Owen Embury; Maud Formanek; Christopher Merchant; Jonathan Mittaz; Joaquín Muñoz-Sabater; Florian Pöppl; Adam Povey; Wolfgang Wagner (Surveys in Geophysics, 2025)
Earth observation data should inform decision making, but good decisions can only be made if the uncertainties in the data are taken into account. Making sense of uncertainty information can be difficult, because uncertainties represent the statistical spread in the observations (e.g., expressed as $$x ± y$$ x ± y ), which does not relate directly to one specific use case of the data. Here, we propose a Bayesian framework to transform Earth observation product uncertainties into actionable information, i.e., estimates of how confident one can be in the occurrence of specific events of interest given the data and their uncertainty. We demonstrate this framework using two case examples: (i) monitoring drought severity based on soil moisture and (ii) estimating coral bleaching risk based on sea surface temperature. In both cases, we show that ignoring uncertainties can easily lead to misinterpretation of the data, making any decisions based on these data unlikely to be the best course of action. The proposed framework is general and can, in principle, be applied to a wide range of applications. Doing so requires a careful dialogue between data users, to formulate meaningful use cases and decision criteria, and data producers, to provide a rigorous description of their data and its uncertainties. The next step would then be to confront the uncertainty-informed estimates of event probabilities (created by the framework proposed here) with the costs and benefits of possible courses of action in order to make the best possible decisions that maximize socioeconomic merit.

Stability of cloud detection methods for Land Surface Temperature (LST) Climate Data Records (CDRs) - Claire E. Bulgin; Ross I. Maidment; Darren Ghent; Christopher J. Merchant (Remote Sensing of Environment, 2024)

Improving the combined use of reflectance and thermal channels for ocean and coastal cloud detection for the Sea and Land Surface Temperature Radiometer (SLSTR) - Claire E. Bulgin; Agnieszka Faulkner; Christopher J. Merchant; Gary K. Corlett; Niall McCarroll; Owen Embury; Edward Polehampton; Connor McGurk (Remote Sensing of Environment, 2023)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Correction to: Global reconstruction of twentieth century lake surface water temperature reveals different warming trends depending on the climatic zone - Sebastiano Piccolroaz; R. Iestyn Woolway; Christopher J. Merchant (Climatic Change, 2020)

Global reconstruction of twentieth century lake surface water temperature reveals different warming trends depending on the climatic zone - Sebastiano Piccolroaz; R. Iestyn Woolway; Christopher J. Merchant (Climatic Change, 2020)

Global in situ Observations of Essential Climate and Ocean Variables at the Air–Sea Interface - Luca R. Centurioni; Jon Turton; Rick Lumpkin; Lancelot Braasch; Gary Brassington; Yi Chao; Etienne Charpentier; Zhaohui Chen; Gary Corlett; Kathleen Dohan; Craig Donlon; Champika Gallage; et al. (Frontiers in Marine Science, 2019)

Observational Needs of Sea Surface Temperature - Anne G. O’Carroll; Edward M. Armstrong; Helen M. Beggs; Marouan Bouali; Kenneth S. Casey; Gary K. Corlett; Prasanjit Dash; Craig J. Donlon; Chelle L. Gentemann; Jacob L. Høyer; Alexander Ignatov; Kamila Kabobah; et al. (Frontiers in Marine Science, 2019)

Substantial increase in minimum lake surface temperatures under climate change - R. Iestyn Woolway; Gesa A. Weyhenmeyer; Martin Schmid; Martin T. Dokulil; Elvira de Eyto; Stephen C. Maberly; Linda May; Christopher J. Merchant (Climatic Change, 2019)

The Copernicus Surface Velocity Platform drifter with Barometer and Reference Sensor for Temperature (SVP-BRST): genesis, design, and initial results - Paul Poli; Marc Lucas; Anne O'Carroll; Marc Le Menn; Arnaud David; Gary K. Corlett; Pierre Blouch; David Meldrum; Christopher J. Merchant; Mathieu Belbeoch; Kai Herklotz (Ocean Science, 2019)
To support calibration and validation of satellite sea surface temperature (SST) retrievals, over 60 high-resolution SST (HRSST) drifting buoys were deployed at sea between 2012 and 2017. Their data record is reviewed here. It is confirmed that sea state and immersion depth play an important role in understanding the data collected by such buoys and that the SST sensors need adequate insulation. In addition, calibration verification of three recovered drifters suggests that the sensor drift is low, albeit negative at around −0.01 K year−1. However, the statistical significance of these results is limited, and the calibration procedure could not be exactly reproduced, introducing additional uncertainties into this drift assessment. Based on lessons learnt from these initial buoys, a new sensor package for the Surface Velocity Platform with Barometer (SVP-B) was designed to serve calibration of SST retrievals by European Union's Copernicus satellites. The novel sensor package includes an HRSST sensor calibrated by a metrology laboratory. The sensor includes a pressure probe to monitor immersion depth in calm water and acquires SST data at 1 Hz over a 5 min interval every hour. This enables the derivation of mean SST as well as several percentiles of the SST distribution. The HRSST sensor is calibrated with an uncertainty better than 0.01 K. Analysis of the data collected by two prototypes deployed in the Mediterranean Sea shows that the buoys are able to capture small-scale SST variations. These variations are found to be smaller when the sea state is well mixed and when the buoys are located within eddy cores. This affects the drifter SST data representativeness, which is an aspect of importance for optimal use of these data.

Geographic and temporal variations in turbulent heat loss from lakes: A global analysis across 45 lakes - R. Iestyn Woolway; Piet Verburg; John D. Lenters; Christopher J. Merchant; David P. Hamilton; Justin Brookes; Elvira de Eyto; Sean Kelly; Nathan C. Healey; Simon Hook; Alo Laas; Don Pierson; et al. (Limnology and Oceanography, 2018)
Heat fluxes at the lake surface play an integral part in determining the energy budget and thermal structure in lakes, including regulating how lakes respond to climate change. We explore patterns in turbulent heat fluxes, which vary across temporal and spatial scales, using in situ high‐frequency monitoring data from 45 globally distributed lakes. Our analysis demonstrates that some of the lakes studied follow a marked seasonal cycle in their turbulent surface fluxes and that turbulent heat loss is highest in larger lakes and those situated at low latitude. The Bowen ratio, which is the ratio of mean sensible to mean latent heat fluxes, is smaller at low latitudes and, in turn, the relative contribution of evaporative to total turbulent heat loss increases toward the tropics. Latent heat transfer ranged from ~ 60% to > 90% of total turbulent heat loss in the examined lakes. The Bowen ratio ranged from 0.04 to 0.69 and correlated significantly with latitude. The relative contributions to total turbulent heat loss therefore differ among lakes, and these contributions are influenced greatly by lake location. Our findings have implications for understanding the role of lakes in the climate system, effects on the lake water balance, and temperature‐dependent processes in lakes.

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

A Review of the Tools Used for Marine Monitoring in the UK: Combining Historic and Contemporary Methods with Modeling and Socioeconomics to Fulfill Legislative Needs and Scientific Ambitions - Tim P. Bean; Naomi Greenwood; Rachel Beckett; Lauren Biermann; John P. Bignell; Jan L. Brant; Gordon H. Copp; Michelle J. Devlin; Stephen Dye; Stephen W. Feist; Liam Fernand; Dean Foden; et al. (Frontiers in Marine Science, 2017)

Warming of Central European lakes and their response to the 1980s climate regime shift - R. Iestyn Woolway; Martin T. Dokulil; Wlodzimierz Marszelewski; Martin Schmid; Damien Bouffard; Christopher J. Merchant (Climatic Change, 2017)

Global climatology of surface water temperatures of large lakes by remote sensing - Aisling Layden; Christopher Merchant; Stuart MacCallum (International Journal of Climatology, 2015)
Lake surface water temperatures ( LSWTs ) of 246 globally distributed large lakes were derived from Along‐Track Scanning Radiometers ( ATSR ) for the period 1991–2011. The climatological cycles of mean LSWT derived from these data quantify on a global scale the responses of large lakes' surface temperatures to the annual cycle of forcing by solar radiation and the ambient meteorological conditions. LSWT cycles reflect the twice annual peak in net solar radiation for lakes between 1°S to 12°N. For lakes without a lake‐mean seasonal ice cover, LSWT extremes exceed air temperatures by 0.5–1.7 °C for maximum and 0.7–1.9 °C for minimum temperature. The summer maximum LSWTs of lakes from 25°S to 35°N show a linear decrease with increasing altitude; −3.76 ± 0.17 °C km −1 ( = 0.95), marginally lower than the corresponding air temperature decrease with altitude −4.15 ± 0.24 °C km −1 ( = 0.95). Lake altitude of tropical lakes account for 0.78–0.83 ( ) of the variation in the March to June LSWT –air temperature differences, with differences decreasing by 1.9 °C as the altitude increases from 500 to 1800 m above sea level (a.s.l.) We define an ‘open water phase’ as the length of time the lake‐mean LSWT remains above 4 °C. There is a strong global correlation between the start and end of the lake‐mean open water phase and the spring and fall 0 °C air temperature transition days, ( = 0.74 and 0.80, respectively), allowing for a good estimation of timing and length of the open water phase of lakes without LSWT observations. Lake depth, lake altitude and distance from coast further explain some of the inter‐lake variation in the start and end of the open water phase.

Heterophil/Lymphocyte Alterations as a Measure of Stress in American Alligators in Relation to Anthropogenic Disturbance in a Louisiana Intermediate Marsh - Christopher Murray; Justin Rheubert; Michael Easter; Mark Merchant; Brian Crother (Journal of Marine Science and Engineering, 2015)
Numerous anthropogenic factors represent environmental threats to Gulf Coast wetland ecosystems and associated fauna. American alligators (Alligator mississippiensis) have been subject to long-term management and used as ecological and physiological indicators of habitat quality in response to anthropogenic events and stochastic natural disasters. The present study monitored heterophil to lymphocyte ratios (an indicator of stress), in American alligators in a Louisiana intermediate marsh from 2009 to 2011, a time period that coincides with an oil inundation event that occurred in 2011. Sixteen alligators were observed and processed morphometrically (total length, snout-vent length and body mass). Heterophil to lymphocyte ratios were negatively correlated with size, suggesting larger American alligators were physiologically more resilient to the disturbance, more able to actively avoid these poor conditions, or are less affected by localized disturbance.

THE GODAE HIGH-RESOLUTION SEA SURFACE TEMPERATURE PILOT PROJECT - Craig Donlon; Kenneth Casey; Ian Robinson; Chelle Gentemann; Richard Reynolds; Ian Barton; Olivier Arino; John Stark; Nick Rayner; Pierre LeBorgne; David Poulter; Jorge Vazquez-Cuervo; et al. (Oceanography, 2009)